Hubungan Kekuasaan Otoritas, Persepsi Keadilan, Kepercayaan Publik, dan Kebijakan Tarif Pajak terhadap Kepatuhan Wajib Pajak pada Badan Pendapatan Daerah Kabupaten Bulungan - Desy Karlisa Mariganto; Rulinawaty Kasmad; Agus Joko Purwanto (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to analyze relationship between power and authority, perception of fairness, public trust, and tax rate policies on taxpayer compliance at the Regional Revenue Agency of Bulungan Regency. The method applied to conduct this research is a quantitative approach method using primary data and secondary data. In this study, the population is taxpayers who have registered and have a 2021 Regional Taxpayer Identification Number (NPWD) of 33,164 taxpayers. The sampling technique in this study was simple random sampling. By using the Slovin formula, the sample obtained is 395 respondents. In this study, data collection techniques were used which included questionnaires, literature studies, and interviews. The data analysis technique used is classical assumption testing and multiple linear regression analysis. The results obtained show that partially there is no significant influence of the tax authorities and tax rate policies on taxpayer compliance. Meanwhile, the variable perception of justice and public trust has a positive and significant relationship to taxpayer compliance. Furthermore, it simultaneously shows that there is a strong relationship between the power of the tax authorities, perceptions of fairness, public trust and tax rate policies on taxpayer compliance at Bapenda Bulungan Regency.